ID 138 – Differentiation of attention network deficits in Mild Cognitive Impairment and Alzheimer's disease by means of auditory oddball fMRI responses. Issue 3 (March 2016) - Assem, Moataz; Alpsan, Meltem Hale; Karahan, Esin; Bayram, Ali; Bilgiç, Başar; Gürvit, Hakan; Ademoglu, Ahmet; Demiralp, Tamer
Abstract : Objective: To investigate the affection of widespread activations elicited by the auditory oddball paradigm in healthy elderly, Mild Cognitive Impairment (MCI) and Alzheimer's disease (AD) in an event related fMRI study. Methods: 5 controls, 6 MCI and 5 AD subjects participated. Paradigm consisted of standard (1000 Hz, 80%) and target (1500 Hz, 20%) stimuli (200 ms, mean ISI 2.2 s). BOLD images (TR = 2400 ms) and T1 anatomical scans were acquired with a 1.5 Tesla system. Standard preprocessing was applied using SPM8. General linear model design matrix included standard (single regressor), target stimuli (two regressors: correct and wrong responses), realignment parameters and time derivatives of hemodynamic function. Results: Areas affected in MCI and AD relative to controls include dorsolateral and ventrolateral prefrontal, anterior cingulate, superior temporal, supramarginal, cuneus, fusiform and lingual gyri. Areas exclusively affected in AD include middle temporal, precuneus gyri, caudate, thalamic nuclei and posterior cingulate cortex. Conclusions: Compared to MCI, AD shows progressive affection of attention related regions, especially those of the dorsal network. In addition, basal ganglia recruitment is only affected in AD. Key message: fMRI responses to auditory oddball can serve as a potential imaging biomarker to differentiate between attention networks deficits in MCI and AD.